The role of ammonia as an alternative fuel by mixing it into natural gas and satisfying the gas quality requirements - Christina Ingo; Jessica Tuuf; Margareta Björklund‐Sänkiaho (Energy Science & Engineering, 2023)
Abstract Ammonia as a carbon‐free e‐fuel has a good potential as a future energy vector to contribute to reducing greenhouse gas emissions. By mixing it into natural gas (NG), the carbon dioxide emissions are decreased when the mixture is burnt. To study the change in the gas properties of different NG compositions with and without added hydrogen, 0–20 mol% ammonia was mixed and various parameters were calculated. The results show that a higher content of ammonia decreases the compression factor, lower heating value, and Wobbe index (WI). Depending on the gas composition the relative density is either increasing, for NGs containing a high level of methane and/or hydrogen, or decreasing, for gases with larger quantities of higher hydrocarbons and/or inert gases. NGs with added hydrogen are more impacted by addition of ammonia, where the relative density can be improved by mixing the gas with ammonia to satisfy the gas quality requirements. However, taking the WI limits into account, more ammonia can be added into a NG without any hydrogen compared to one with hydrogen. The addition of ammonia into NG is possible considering the gas quality parameters, even in the case when the gas contains some hydrogen.